Os sentidos de qualidade nas políticas curriculares para o ensino médio no estado do Rio Grande do Sul (1991-2014) - Silveira, Emerson Lizandro Dias (Universidade do Vale do Rio dos Sinos, 2020)
This research aimed to examine the meanings of quality emerging from curricular policies for high school in the state of Rio Grande do Sul in the period between 1991 and 2014. The methodology of documentary analysis was based on theoretical assumptions derived from the sociology of contemporary education, mainly in the contributions of Young (2014) and Ball (2013) on the field of Curriculum Studies in an international economic-political context, marked by the close relationship between the market and education. As a result, it is emphasized that, during the analysis period, the different curricular policies put into practice aligned with an international context, marked by the influence of economic rationality in the curriculum, both in teacher training and in assessment systems. Added to this is a wide discursiveness around the concept of quality of education, which permeated the respective educational policies, carried out by governments of different ideological nuances that took turns in power between 1991 and 2014 in the State of Rio Grande do Sul (Brazil), sometimes assuming meanings linked to the academic performance of students and institutions, sometimes linked to meanings of social quality, with a strong social concern and citizen agenda. It adds the fact that each policy put into practice suffers a rupture due to the alternation of governments, making it impossible to achieve its objectives. Thus, it was observed that, even assuming meanings of quality that are sometimes antagonistic, the analyzed policies show similarity in defining processes that went against the regulation and typical market control, signaled by the international agencies that redirected the role of the school since the 1990s. At the end of the study, it is argued that the quality of Secondary Education in Brazil is a horizon to be pursued and can, in fact, only be realized with the hybridization of the two senses, namely: the acceptance of demands and the defense of knowledge with a focus on students' academic performance.
Keywords: Ensino médio; Currículo; Qualidade da educação; Rio Grande do Sul; High school; Curriculum; Quality of education; Rio Grande do Sul; ACCNPQ::Ciências Humanas::Educação